Analisis Realisasi Pendapatan Daerah Kabupaten Tanah Datar Tahun 2024: Kinerja Fiskal, Efektivitas Pengelolaan PAD, dan Tantangan Kemandirian Keuangan Daerah - Y, Angye Mareta; Frinaldi, Aldri; Asnil, Asnil; Putri, Nora Eka (LPPM Institut Pendidikan Nusantara Global, 2025)
This study analyzes the 2024 regional revenue performance of Tanah Datar Regency, focusing on the effectiveness of Local Own- Source Revenue (PAD) management, dependency on transfer revenues, and implications for fiscal independence. Data were obtained from the 2024 Regional Revenue Realization Report published by the local government and analyzed using a qualitative descriptive approach by comparing budget targets and realizations. The total revenue was budgeted at IDR 1.36 trillion, with a realization of IDR 1.33 trillion (97.3%), indicating high effectiveness. PAD achieved 99.14%, showing strong local revenue management, mainly from regional asset utilization and other legitimate sources. However, transfer revenues accounted for about 88%, reflecting high dependency on the central government. Despite effective fiscal performance, financial independence remains low. Strategic measures such as expanding the tax base, digitizing revenue collection, optimizing regional assets, and developing local potentials like tourism, agriculture, and creative industries are essential to strengthen fiscal capacity and achieve sustainable regional independence.